2021
DOI: 10.1016/j.jss.2021.02.054
|View full text |Cite
|
Sign up to set email alerts
|

Initial Outcomes of a Novel Irrigating Wound Protector for Reducing the Risk of Surgical Site Infection in Elective Colectomies

Abstract: Background: Surgical site infection (SSI) rates in elective colorectal surgery remain high due to intraoperative exposure of colonic bacteria at the surgical site. We aimed to evaluate 30-day SSI outcomes of a novel wound retractor that combines barrier protection with continuous wound irrigation in elective colorectal resection. Materials and methods:A retrospective single-center cohort-matched analysis included all patients undergoing elective colorectal resection utilizing the novel irrigating wound protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…Though some in‐vitro studies 39,40 have shown a negative outcome of povidone‐iodine on tissue regeneration, some old studies label serum iodine toxicity as an outcome of irrigation 41,42 . Though, these adverse effects cannot be validated in clinical trials 13‐36 . When considering antibiotics, however, our results favour its use, the bactericidal influence of most agents needs a contact time.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Though some in‐vitro studies 39,40 have shown a negative outcome of povidone‐iodine on tissue regeneration, some old studies label serum iodine toxicity as an outcome of irrigation 41,42 . Though, these adverse effects cannot be validated in clinical trials 13‐36 . When considering antibiotics, however, our results favour its use, the bactericidal influence of most agents needs a contact time.…”
Section: Discussionmentioning
confidence: 81%
“…A total of 1867 distinctive studies were found, of which 24 studies (between 1979 and 2021) satisfied the inclusion criteria and were comprised in the study. 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 This meta‐analysis study based on 24 studies included 4967 subjects under surgery at the start of the study; antibiotic irrigation was used with 1372 of them, 1261 were aqueous povidone‐iodine irrigation, and 2334 were saline irrigation or no irrigation for surgical site infections prevention in all surgical populations. All studies evaluated the effect of wound irrigation on the prevention of surgical site infections.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pacientes com história clínica de diabetes, imunossupressão, associados a fatores correlatos como ambiente e a utilização restrita de técnica estéril, o ambiente e o tempo de cirurgia pode incidir em maiores riscos (SCHWARTZMAN; KHACHEMOUNE, 2021). Os processos multifatoriais incluem, as infecções do sítio cirúrgico que permanecem como um sério agravo, com aumento na morbidade, tempo de internação hospitalar, readmissões, aumento dos custos hospitalares (MALEK et al, 2021).…”
Section: Introductionunclassified